Rheumatoid Arthritis: Current and Emerging Paradigms of Diagnosis and Treatment: Pharmaceutical sciences- Pharmaceutics - Kaur, Rajni; Kumar Dewangan, Hitesh (International Journal of Life Science and Pharma Research, 2023)
Rheumatoid arthritis (RA) is a chronic autoimmune disorder characterized by inflammation and damage to joints andtissues. While previous reviews exist, there still needs to be more in understanding risk factors, diagnostic methods, and treatmentoptions. This review aims to fill these gaps by providing a comprehensive overview of recent advancements in the field. To addressthe limitations of previous reviews, this article incorporates updated information on risk factors, including the influence ofenvironmental factors in industrialized nations. It highlights the significance of early RA diagnosis and emphasizes the utility ofdynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) for effective disease management. Moreover, this reviewintroduces innovative nanotechnology-based treatment approaches for RA. It explores the potential of gold nanoparticles, carbonnanotubes, polymer-based nanomedicine, and nanoliposomes in targeting specific inflammatory sites and improving treatmenteffectiveness. This review aims to present an up-to-date and comprehensive analysis of RA, bridging gaps in previous literature byintroducing novel diagnostic techniques and exploring emerging treatment modalities. By synthesizing current knowledge andoutlining future research prospects, this review aims to advance the understanding and treatment of rheumatoid arthritis.Additionally, this review discusses the systemic complications associated with RA, such as rheumatoid vasculitis and Feltysyndrome. It also sheds light on the long-term consequences of untreated RA, including the potential need for joint replacementsurgery (arthroplasty) and splenectomy. By providing a comprehensive analysis of these aspects, this review aims to enhance theholistic understanding of RA and guide future research toward improved management and patient outcomes.